The e-Leaders Handbook on the Governance of Digital Government. - OECD.; ProQuest (firma) (Paris : Organization for Economic Cooperation & Development, 2022)
The digital transformation of public sectors, economies and societies is generating challenges as well as opportunities for governments. Robust public governance is needed to respond to these challenges, reap the full benefits of digital and data-driven government, and encourage a holistic, systemic transformation.
Dimension 3.2 Project Management Tools -- Sub-Dimension 3.2.1 Value Proposition - Business Cases -- Sub-Dimension 3.2.2 Agile Project Management -- Sub-Dimension 3.2.3 Procurement of ICT/Digital Technologies -- Dimension 3.3 Financial Management Mechanisms -- Sub-Dimension 3.3.1 Budgeting/Budget Threshold -- Sub-Dimension 3.3.2 Co-Funding -- Dimension 3.4 Regulation and Standards -- Sub-Dimension 3.4.1 Regulatory Frameworks -- Sub-Dimension 3.4.2 Standards, Principles and Guidelines -- Sub-Dimension 3.4.3 Regulatory Co-operation with Industry Players -- References -- Blank Page.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2022. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: elektronické knihy; electronic books